Prenatal Ultrasound Utilization and Its Associated Factors among Pregnant Women in Jimma Town Public Health Institutions, Ethiopia - Aynalem Yetwale; Tola Kabeto; Tsegaw Biyazin; Belete Fenta (SAGE Publishing, 2022)
Background Ultrasound scanning is an integral part of antenatal care worldwide. However, little is known about the utilization of obstetric ultrasound in Ethiopia. This study aimed to assess prenatal ultrasound utilization and its associated factors among pregnant women attending antenatal care in Jimma town public health care facilities. Methods An institutional-based cross-sectional study was conducted on 303 pregnant women attending antenatal care (ANC) from July to August 2021 in Jimma town public health care facilities. A systematic sampling technique was used to select study participants who attended the ANC service during the data collection period. Logistic regression analysis was performed to determine the association between the explanatory and response variables. The strength of association of dependent and independent variables was presented as crude and adjusted odds ratio (AOR) at a 95% confidence interval. The level of significance was declared at a P -value of less than .05 in multivariable logistic regression. Narratives, figures, and tables were used to obtain the results. Findings The proportion of prenatal ultrasound utilization in this study was 60.7% [(95% CI); (55.4%-66%)]. Residency AOR = 6.09 (95%CI: 2.35-15.78), household monthly income less than 1000 AOR = 0.159(0.035-0.73), mother's history of at least one abortion AOR = 5.78 (95% CI: 1.89- 17.64), and knowledge towards prenatal ultrasound AOR = 15.77 (95% CI: 6.39-38.92) were found statistically significant association with prenatal ultrasound utilization. Conclusions In the current study, the proportion of prenatal ultrasound utilization during pregnancy was lower than the world health organization (WHO) recommendation. Therefore, the author recommended that educating mothers on the purposes of obstetric ultrasound and/ or including a prenatal ultrasound screening as part of antenatal care is needed.